Activation Energy of Extracellular Enzymes in Soils from Different Biomes - Steinweg, J. Megan (Public Library of Science, 2013)
Enzyme dynamics are being incorporated into soil carbon cycling models and accurate representation of enzyme kinetics is an important step in predicting belowground nutrient dynamics. A scarce number of studies have measured activation energy (E(a)) in soils and fewer studies have measured E(a) in arctic and tropical soils, or in subsurface soils. We determined the E(a) for four typical lignocellulose degrading enzymes in the A and B horizons of seven soils covering six different soil orders. We also elucidated which soil properties predicted any measurable differences in E(a). β-glucosidase, cellobiohydrolase, phenol oxidase and peroxidase activities were measured at five temperatures, 4, 21, 30, 40, and 60°C. E(a) was calculated using the Arrhenius equation. β-glucosidase and cellobiohydrolase E(a) values for both A and B horizons in this study were similar to previously reported values, however we could not make a direct comparison for B horizon soils because of the lack of data. There was no consistent relationship between hydrolase enzyme E(a) and the environmental variables we measured. Phenol oxidase was the only enzyme that had a consistent positive relationship between E(a) and pH in both horizons. The E(a) in the arctic and subarctic zones for peroxidase was lower than the hydrolases and phenol oxidase values, indicating peroxidase may be a rate limited enzyme in environments under warming conditions. By including these six soil types we have increased the number of soil oxidative enzyme E(a) values reported in the literature by 50%. This study is a step towards better quantifying enzyme kinetics in different climate zones.